Experimental modeling of sudden death pathological mechanisms in Na+ channel blocker treatment - V. M. Moroz; T. N. Lipnitsky (Российский кардиологический журнал)
In laboratory rats, a minimal arrhythmogenic dose of 1, 5 % KCl solution (15 mg/kg) was injected intravenously in 2 seconds. Hypopolarization arrhythmias were registered in 3-10 seconds, followed by regular sinus rhythm. In experimental groups, the animals received a minimal arrhythmogenic dose of KCl in 5 minutes after intravenous infusion of 1 % novocainamidum (20 mg/kg) or 0, 25 % ethacyzin (4 mg/kg). In all 20 rats, N a+ cannel blocker and KCl bolus administration resulted in cardioplegy; in every second animal, asystolia and death were registered (40 % and 60 %, respectively). Therefore, in coronary heart disease patients, receiving Na+ channel blockers, sudden death pathogenesis might be influenced by membrane hyperpolarization, due to Na+/K+-ATPase dysfunction, low cytosol concentration of K+ ions, and their decreased flow from the cells in final repolarization phase.